Ideology in Portraying the Israeli onslaught on Gaza in August 2022: A Transitivity Analysis of The Hindu and the Washington Post Reports - M. A. Abunahel, Mohammed (South Asian Journal of Social Sciences and Humanities, 2023)
This critical discourse analysis (CDA) investigates how The Hindu and the Washington Post (WP) construct their online news in depicting the Israeli onslaught on Gaza in August 2022. Halliday’s transitivity system was adopted to explore the hidden ideologies and analyze the textual choice or words’ features in the clauses of thirteen (13) news articles from The Hindu and nine (9) from WP. The study’s findings indicate that the most dominant processes in both news media were the verbal and material processes. Within the verbal process, it was divided into three sides: Palestinian, Israel and neutral. The findings reveal that both media have common strategies to represent the Israeli and neutral verbal process, while the selected media share similarities and differences in representing the Palestinian verbal process. The findings through the material process suggest that both media show Israel as an actor more than as a goal. They tend to use processes ‘verbs’ that are associated with extreme violence and less violence with Israel, whereas Palestinian are associated with less violence process, but the process is supported with adjectives, adverbs and numbers to place it in extreme violence. The analysis is then followed by the revealed methods and techniques used by the selected media. Overall, both news media have hidden ideologies to construct their news articles. Based on these empirical evidences, (CDA) appears to play an essential part in understanding the language that is employed in media discourses.